2022
DOI: 10.3389/frph.2022.812053
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan (CPT-11) Treatment Induces Mild Gonadotoxicity

Abstract: Background:Gonadal toxicity following chemotherapy is an important issue among the population of young cancer survivors. The inhibitor of DNA topoisomerase I, irinotecan (CPT-11), is widely used for several cancer types. However, little is known about the effect of irinotecan on the fertility of both genders. Thus, the aim of the present study was to evaluate irinotecan gonadotoxicity, using a mouse model.MethodsMature male and female mice were injected intraperitoneally with either saline (), irinotecan (100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We have validated this method in previous studies. 21 23 The use of TUNEL and its range as apoptotic index is familiar to us from a number of previous studies. In our extensive experience, even with very testicular-toxic agents (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have validated this method in previous studies. 21 23 The use of TUNEL and its range as apoptotic index is familiar to us from a number of previous studies. In our extensive experience, even with very testicular-toxic agents (e.g.…”
Section: Methodsmentioning
confidence: 99%
“… 25 It was previously shown that qPCR may serve as precise tool to measure mRNA of transcription factors that are expressed exclusively in undifferentiated spermatogonia, namely ID4 or GFRA1. 23 , 24 , 26 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, irinotecan has achieved the greatest success in clinical application and market due to its excellent efficacy. Irinotecan, the standard therapeutic agent of the first-line treatment for advanced or metastatic CRC, is bio-activated to 7-ethyl-10-hydroxy-camptothecin (SN38) by carboxylesterase in vivo ( Si et al, 2019 ; Levi et al, 2022 ). The main side effects of irinotecan that include diarrhea and neutropenia require dose reduction or even withdrawal ( Aiyangar et al, 2010 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%